Odpowiedzi

2010-01-06T20:31:58+01:00
X+4y=11
2x+5y=10

x+4y=11/*-2
2x+5y=10

-2x+-8y=-22
2x+5y=10

-3y=-11
y=-3,(66)

x+4*3,66=11
x=3,64

4x+5y=-4
6x+7y=-6

4x+5y=-4/*-7
6x+7y=-6/*5


-28x-35y=28
30x+35y=-30

2x=-2
x=-1

-28*(-1)-35y=28
28-35y=28
y=0

9x+8y=1
5x+6y=11

9x+8y=1/*-6
5x+6y=11/*8

-54x+-48y=-6
40x+48y=88

-6x=82
x=-13,66

40*13,66+48y=88
54,4+48y=88
y=0,7
1 5 1
2010-01-06T20:46:12+01:00
X+4y=11
2x+5y=10
wyznaczamy x z pierwszego równania:
x=11-4y
podstawiamy do drugiego:
2(11-4y)+5y=10
22-8y+5y=10
-3y=10-22
-3y=-12/ :(-3)
y=4

wracamy do wyznaczonego x i podstawiamy y:
x=11-4y
x=11-4*4
x=11-16
x=-5

spr.
x+4y=11 -5+4*4=-5+16=11
2x+5y=10 2*(-5)+5*4= -10+20=10




4x+5y=-4 / *(-7)
6x+7y=-6 /*5

-28x-35y=28
30x+35y=-30

-28x+30x-35y+35y=28-30
2x=-2 /:2
x=-1

4x+5y=-4 → 4*(-1)+5y=-4
-4+5y=-4
5y=-4+4
5y=0
y=0

spr:
4x+5y=-4 → 4*(-1) +5*0=-4 → -4+0=-4
6x+7y=-6 → 6*(-1)+7*0=-6 → -6+0=-6




9x+8y=1 /*(-5)
5x+6y=11 /*9

-45x-40y=-5
45x+54y=99

-45x-40y+45x+54y=-5+99
14y=95/ :14
y=6 i 11/14

9x+8y=1 /*(-6)
5x+6y=11 /*8

-54x-48y=-6
40x+48y=88
-54x+40x=-6+88
-14x=82/:(-14)
x=-82/14
x=-5 i 12/14